High Value Manufacturing in the UK: A Study of its Challenges, Opportunities and Emerging Technologies - Featherston, C.R.; Gregory, M.J.; Gill, A.; O’Sullivan, E. (Applied Science and Engineering Progress, 2013)
The High Value Manufacturing (HVM) Catapult is a collection of manufacturing research centres designed by the UK government to help foster and develop manufacturing in the UK. The Landscape project will inform the manufacturing strategy adopted by the UK Government and its HVM Catapult. The intention is for these results to continue to inform strategy and public policy development in the UK. The Landscape project endeavoured to explore current and future environments by identifying the trends, drivers and challenges in UK manufacturing and the technologies and their related capabilities that could be at the leading edge of manufacturing in 2025. This paper outlines the process that was undertaken to develop the current and future global ’landscape’ of manufacturing. The project identified dozens of capabilities that UK firms could develop to be competitive in manufacturing, given the challenges and emerging technologies facing the industry. It also identified national competencies that could be developed to foster the growth of industrial commons in the UK. This paper will present the project’s major outcomes, highlighting the opportunities in UK manufacturing